Analisis Pembelajaran Biologi dalam Pespektif Inkuiri pada Pembelajaran Menggunakan Kurikulum Kerangka Kualifikasi Nasional Indonesia (KKNI) - Wasis Wuyung Wisnu Brata; Cicik Suriani (Jurnal Pendidikan Biologi, 2018)
The application of the new curriculum directs more scientific learning by applying the six task method. However, curriculum changes often have obstacles in their implementation. This study aims to analyze the learning environment in biology classes from the perspective of inquiry learning, as one of the most recommended science learning approaches. The research uses descriptive methods, with a population of 121 students from five environmental biology classes who have fully implemented the IQF curriculum. Samples taken by cluster random sampling method obtained two classes with a total of 46 students. Data obtained from questionnaires and learning outcomes documents. The results showed that biology learning activities had a level of conformity with inquiry learning in the "sufficient" category. Data shows that among the components of inquiry activity observed, questioning and hypothesizing are the lowest intensity activities. While communication activities have the highest intensity. It can be concluded that the learning of environmental biology still needs to be improved, especially in questioning and hypothesizing activities.